Effect of arboring shading on surface temperature and energy flow on different urban coverings in Cuiabá-MT - RIBEIRO, KARYN FERREIRA ANTUNES; VALIN JR, MARCOS DE OLIVEIRA; Chegury, Juliana Queiroz Borges de Magalhães; Santos, Flávia Maria de Moura; Rodrigues, Thiago Rangel; Curado, Leone Francisco Amorim; Nogueira, José de Souza (Sociedade & Natureza, 2018)
Human actions have contributed to the thermal changes in urban environments on a microclimatic scale through types of coatings that have properties of storing and transmitting energy. One of the strategies of thermically improving cities is the implementation of afforest. Thus, the objective of this study was to analyse the effect of tree shade on the surface temperature and energy flux of different urban coverages in the dry and rainy season in the city of Cuiabá-MT. As a reference, a site was used without afforestation with these same coatings. Analyses of surface temperature, temperature and relative humidity were collected at 08h, 14h and 20h. The non-parametric Bootstrap technique was used for comparisons of surface temperatures. The results indicate that the woody scenarios showed a "cooling" in relation to the unshaded surfaces, indicating the importance of arboreal shading for the mitigation of the elevation of temperature, especially in the afternoon, during which time the greatest differences in surface temperatures occurred between the hose and non-afforestation scenarios, with emphasis on asphalt material up to 15 ° C difference in the dry period. In this context it is important to highlight the influence of solar radiation on the results of surface temperatures and types of building materials used in cities. Thus, this study was able to relate important variables to the characterization of the local urban environment, suggesting that the afforestation in this environment is fundamental for the mitigation of surface temperature elevation.